Determinants of Inter-Governmental Cooperation in the Greater Jakarta Area, Indonesia - Dicky Irawan; M. Didi Turmudzi; Yaya Mulyana (Pasundan Social Science Development, 2022)
This research was determined to analyze the collaboration concept execution between the regional governments in the Jabodetabekjur regions, Indonesia. The research consists of four variables; (1). starting conditions; (2). facilitative leadership; (3). institutional design ; and (4). collaborative process. Structural Equation Model (SEM) with SmartPLS is being used to analyze the data. The 87 respondents’ information were collected from various government institutions within the Jabodetabekjur regions. The results show that the collaboration amongst the government institutions in Jabodetabekjur regions were not effectively executed, due to the imbalance resources in the starting condition phase. It is shown that the DKI Jakarta (Special Capital Region of Jakarta) has more dominant financial resource that other regions.